1998
DOI: 10.1097/00005373-199807000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness and Limitations of Ultrasonography in the Initial Evaluation of Blunt Abdominal Trauma

Abstract: US is reliable for the detection of injuries and the identification of solid-organ injuries despite its poor sensitivity for intestinal injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 21 publications
6
75
0
7
Order By: Relevance
“…Yoshii et al [10] concluded from their study that ultrasound has poor sensitivity for intestinal injuries and found that the sensitivity, specificity and accuracy were 34.7, 99.9 and 97.3% respectively. Similarly Malhotra et al [8] stated that ultrasound fails in the diagnosis of specific injury causing the fluid and is poor in the detection of hollow viscus injury.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshii et al [10] concluded from their study that ultrasound has poor sensitivity for intestinal injuries and found that the sensitivity, specificity and accuracy were 34.7, 99.9 and 97.3% respectively. Similarly Malhotra et al [8] stated that ultrasound fails in the diagnosis of specific injury causing the fluid and is poor in the detection of hollow viscus injury.…”
Section: Discussionmentioning
confidence: 99%
“…Underlying this paradigm is the understanding that ongoing evaluation through serial examinations or other imaging will be needed to determine whether a patient has any intra-abdominal injury. Most experts would concur that ultrasound has performed best when limited to detecting free intraperitoneal fluid [10,11,19]. Historically, the presence of any intraperitoneal fluid indicated a significant intra-abdominal injury and warranted an immediate exploratory laparotomy.…”
Section: Clinical Implications Of the Focused Assessment With Sonogramentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Technique varies widely among trauma centers. The examination may consist of a brief survey for fluid alone, or it may include assessment of organ parenchyma.…”
mentioning
confidence: 99%
“…Many authors use free fluid as the only criterion for a positive finding, [1][2][3][4][5][6][7][8][9][10][11][12][13] whereas some describe findings other than fluid as suggestive of traumatic injury as well. [14][15][16][17][18] The inability to show injury without hemoperitoneum has been shown to be a limitation of ultrasonography and may occur in 29% to 34% of patients with injuries caused by BAT. 12,13 The purpose of this study was to determine the benefit of screening for parenchymal abnormalities as well as free fluid during screening abdominal ultrasonography in patients with blunt trauma.…”
mentioning
confidence: 99%